A novel cobalt-free and CO2-stable LDC-LSCF membrane with high oxygen permeability. Issue 1 (2022) - Zhang, Xinle; Chen, Tianyi; Xu, Yongjun; Sun, Chenghua; Wu, Chengzhang
Abstract : Cobalt (Co)-free and carbon dioxide (CO2 )-stable Ce0.8 La0.2 O2− δ –La0.1 Sr0.9 Cu x Fe1− x O3− δ (LDC-LSCF) dual-phase oxygen-permeable membranes have been successfully developed through the one-pot ethylenediaminetetraacetic acid–citric acid method. The appropriate amount of copper (Cu) doping can increase the content of oxygen (O) vacancies and improve the oxygen (O2 ) permeability of the materials. At 900°C, the oxygen permeation flux of 60 wt.% Ce0.8 La0.2 O2− δ –La0.1 Sr0.9 Cu0.2 Fe0.8 O3− δ (60LDC-LSCF-0.2) membrane reaches 0.58 (ml/min)/cm 2 with pure helium (He) as the sweep gas, which is the highest oxygen permeation flux among dual-phase membranes with different copper-doping contents. The effects of different LDC contents on the static stability, conductivity and oxygen permeability of the dual-phase membranes are studied. The oxygen permeation flux of the 60LDC-LSCF-0.2 membrane remains 0.37 (ml/min)/cm 2 with pure carbon dioxide as the sweep gas during the long-term oxygen permeation test. The present results indicate that LDC-LSCF oxygen-permeable membranes are promising membranes for oxygen production and carbon dioxide capture.